Theoretical Implications of Theory Planned Behavior on Purchasing Decisions: A Bibliometric Review - Simanjuntak, Mariana; Putra, Aditya Halim Perdana Kusuma (Golden Ratio of Mapping Idea and Literature Format, 2021)
This study uses a bibliometric literature review approach with a sample mapping literature of 10 articles regarding planned behavior theory approaches to purchase decisions; Reference articles from 2007 - 2021 under publisher Elsevier (e.g., LWT, Journal of Retailing and Consumer Services, Journal of Interactive Marketing, Regional Science and Urban Economics, Food Quality and Preference Journal, Energy Policy, Decision Support Systems Journal, and Industrial Marketing Management ). Universally, the results of this literature study state two propositions and hypotheses (e.g., Firstly, the theoretical implication states that there is a robust theoretical correlation between the theory of Planned behavior on purchase decisions; secondly, the correlation of planned behavior theory in aspects of management (e.g., marketing, Technology, and HRM) make a positive contribution as a grounded theory to explain antecedent variables and their correlation to other approaches)